2016
DOI: 10.1002/fld.4262
|View full text |Cite
|
Sign up to set email alerts
|

An improved ghost‐cell immersed boundary method for compressible flow simulations

Abstract: SUMMARYThis study presents an improved ghost-cell immersed boundary approach to represent a solid body in compressible flow simulations. In contrast to the commonly used approaches, in the present work ghost cells are mirrored through the boundary described using a level-set method to farther image points, incorporating a higher-order extra/interpolation scheme for the ghost cell values. A sensor is introduced to deal with image points near the discontinuities in the flow field. Adaptive mesh refinement (AMR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…With the approaches provided in the last 2 subsections, both the Dirichlet and Neumann boundary conditions can be enforced in the ghost points via the approximation along the line normal to the solid wall. In traditional method, 22,26 the boundary conditions for compressible inviscid flow past solid problems are…”
Section: The Gcib Methods For Compressible Inviscid Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…With the approaches provided in the last 2 subsections, both the Dirichlet and Neumann boundary conditions can be enforced in the ghost points via the approximation along the line normal to the solid wall. In traditional method, 22,26 the boundary conditions for compressible inviscid flow past solid problems are…”
Section: The Gcib Methods For Compressible Inviscid Flowmentioning
confidence: 99%
“…For implementation, the layer number of the ghost points depends on the numerical schemes. [20][21][22] However, we have found that using the points far from the surface will increase the error caused by the extrapolation especially when more than one layer of the ghost points are involved for imposing the boundary conditions. The unknown variables of the ghost points are calculated by the symmetrically mirrored points, while the variables at the mirror points can be obtained through the interpolation of the surrounding fluid point.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure , all of the above‐mentioned flow structures are well captured by the present method. We refer to Woodward and Colella and Chi et al for similar results obtained with a grid‐aligned method.…”
Section: Resultsmentioning
confidence: 59%
“…The computed results for the mass density along the wedge surface are shown in Figure for simulations performed using 400 × 200, 500 × 250, 600 × 300, and 800 × 400 uniform grids. The presently computed results are compared with the grid‐aligned solutions of Chi et al who used a rotational transformation technique and assumed that the shock wave moves at an angle of 60° to the x 1 ‐axis and the domain boundary at the bottom is reflective from x = 1/6. This configuration does not require dealing with the cut‐cell problem of the wedge surface and can be used as a reference for comparison.…”
Section: Resultsmentioning
confidence: 99%